Transaction costs and the marketable surplus of milk in smallholder farming systems of The Gambia - Somda, Jacques; Tollens, E.F.; Kamuanga, M. (SAGE Publications, 2005)
The neoclassical economic paradigm views market linkages as efficient mechanisms for trading. However, the validity of this position is questionable, as markets frequently do not possess the structural conditions necessary for perfect competition. In subsistence-farming systems, factors that prevent greater participation of smallholders in markets can be found from the production level to the access to markets themselves. This study investigates the transaction-cost factors operating in smallholder dairy farms in The Gambia. The results indicate that access to market at the farm gate, the number of local cows and the distance to the nearest city increase the likelihood of market participation by producers and the marketing of surpluses of dairy products. Increases in home consumption lead to decreases in sales and of farmers' participation in milk marketing. To achieve pro-poor rural growth, it is therefore essential to address explicitly the low productivity of dairy cattle, low capital endowments and market accessibility for smallholder farmers.